Pentingnya Ethos Kerja dan Etika Serta Dampaknya Terhadap Profesi dan Perkembangan Karir Seseorang di Dunia Kerja - Mesalaen, Ilham; Angraini, Alena Puspita; Sya’diah, Zahra Asfa; Rukmasara, Rif’at Rafi; Zulaikha, Royan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Work ethic and professional ethics are two fundamental components that influence the quality of individual performance and determine the direction of a person's career development in the modern workplace. A dynamic work environment requires workers to have not only technical competence, but also moral integrity and a consistent professional attitude. This study aims to analyze the role of work ethic and professional ethics and their impact on a person's profession and career development. The research method used is a literature study with a descriptive qualitative approach, using four relevant scientific journals as the main sources. The results of the study show that a high work ethic—characterized by commitment, responsibility, discipline, and quality orientation—is directly correlated with increased productivity, organizational trust, and career advancement opportunities. In addition, the internalization of professional ethics affects work reputation, professional stability, and long-term career sustainability. In conclusion, work ethic and professional ethics are important prerequisites for building a successful and sustainable career.